Efeito do Ranelato de Estrôncio em cultura bidimensional de osteoblastos primários e imortalizados, e em cultura tridimensional, sobre scaffolds de Osso Bovino Trabeculado - Cristiane Aparecida de Sousa (2014)
Understanding the mechanisms that control osteogenesis, as well as drugs and biomaterials that promote bone repair, is of fundamental importance for the establishment of new therapies for bone reconstruction, representing the pillars of tissue bioengineering. Biomaterials made up of bovine bone have unveiled promising results as arrays for bone filling. Drugs, such as Strontium Ranelate (SR), have demonstrated significant anti-osteoporotic effects, and have been indicated for oral administration for prevention of bone fractures, especially for post-menopausal women. However, so far, few studies have investigated SR local effects, and its use in association with biomaterials. In this work, we investigated SR effects in cultures of primary osteoblasts (PO) obtained from Wistar rats neonates cranial calottes and immortalized osteoblasts (IO) MC3T3- E1 cell line, cultivated in monolayer, or in association with bovine bone as scaffolds, as mineralized (MBB) and demineralized (DBB) forms, to evaluate if these associations would promote in vitro cell performance. We chose to work with SR (p.a.), using medium without supplementation, to verify its action without the interference of other reagents. SR effect on cell viability (MTT) was determined using a dose-effect curve, with dosis ranging from 0.025 to 1 mM. After establishing 0.1 mM as the optimum dose, the effects of the SR local administration in osteoblasts were evaluated during the following phases: 1. cell differentiation (by measuring alkaline phosphatase activity, and by qRT-PCR, using Runx2, Collagen I, FGFR1 and Osteocalcin as osteogenic differentiation markers); 2. deposition of organic matrix (using picrosirius red Collagen staining); and 3. deposition of mineralized matrix (using alizarin red staining). Cell viability of osteoblasts cultivated onto MBB and DBB scaffolds were also obtained using the MTT assay. Our results suggested that SR is biocompatible, improves PO and IO metabolism, and did not present a cytotoxic effect when it is administrated in loco. Besides, SR appeared to accelerate cell differentiation, enhancing alkaline phosphatase activity, the expression of osteogenic differentiation markers, and the synthesis of organic matrix. During the mineralization phase, the Ca2+ content decreased in the group treated with SR in relation to the control, probably associated with Strontium competition during the hydroxyapatite formation. DBB showed to be better scaffolds for PO and IO. Our results indicated the importance to further investigate the local administration of SR at sites of bone repair. The success of the association of SR and DBB signalized the possibility of using SR as co-adjuvant for bone tissue bioengineering, and in therapies of bone filling with other biomaterials.